Contrasting genetic, acoustic, and morphological differentiation in two closely related gladiator frogs (Hylidae: Boana) across a common Neotropical landscape - Escalona S., Moisés D.; Juncá, Flora Acuña; Giaretta, Ariovaldo A.; Crawford, Andrew J.; Marca, Enrique La (Zootaxa, 2019)
Mountain chains and rivers are often found to represent barriers promoting vicariant differentiation in terrestrial vertebrates. Previous studies have supported the idea that the Cordillera de Mérida (CM), the easternmost branch of the Northern Andes, represents a geographic barrier for vertebrates, including frogs. Previous studies have also suggested that the Orinoco River (OR), the biggest river in Venezuela, also represents a geographic barrier for terrestrial vertebrates. Boana pugnax and B. xerophylla are two Neotropical hylids, members of the B. faber species group, that are distributed on either side of the CM, and whose ranges extend up to 605 and 2450 m in elevation, respectively. In addition, B. xerophylla occurs on either side of the OR. Herein, we assess the genetic, acoustic, and morphological differentiation within B. pugnax and within B. xerophylla across the CM and within B. xerophylla across the OR, and test if genetic differentiation is correlated with geographic distance. We also evaluated the acoustic differentiation between the recently recognized B. xerophylla and its sister species, B. crepitans, and found marked differences between advertisement calls, corroborating their status as distinct species. Genetic and morphometric analyses of populations from opposite sides of the CM revealed differentiation in B. pugnax but not in B. xerophylla. Within the latter species, we found molecular, acoustic, and morphometric differentiation among samples of B. xerophylla from western Venezuela versus the Guiana Shield. Genetic variation within B. pugnax and within B. xerophylla was not explained by geographic distance. Thus, our data show conspecific population structure across the CM in B. pugnax, plus the possible existence of two species within what today is considered B. xerophylla, yet the CM apparently is not involved in this divergence. These results suggest that even for closely related species with shared ecology and distribution, genetic and phenotypic differentiation respond differently to common ecological or historical factors.